A Study on Prediction of Output in Oilfield Using Multiple Linear Regression - Izni binti Mustafar, IM (Centre For Promotion Ideas (CPI), USA, 2011)
An oilfield is an area with reserves of recoverable petroleum, especially one with several oil-producing wells [1]. The challenge in this project is to find the variable for the output of oilfield because here are numerous factors affecting output in an oilfield. The relationship between field output and one of the affecting factors is unscientific and are not precise, which it is needed to come out with a simple and more accurate. 8 parameters have been identified to predict the oilfield of output. After several screening test using Multiple Linear Regression, 4 parameters have been identified as a most significant parameter. The ordinary least squares method also used to minimize the sum of variables by eliminating the least important variables. And to validate the data, new set of different data used with only the most significant parameters. It validates the method as all the parameters obey the rules of P-value.